PENINGKATAN HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR MELALUI MODEL FLIPPED CLASSROOM PADA PEMBELAJARAN DARING - Nadia Isnainita; Ika Septiana; Elis Dwi Purbiyanti (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract :The purpose of this study is to describe the increase in cognitive learning outcomes of third grade students of SDN 4 Telukwetan through the flipped classroom model in online learning of Theme 8 Praja Muda Karana. The subject of this classroom action research is the cognitive learning outcomes of 22 students who are supported by the quality of the learning process. Data collection in this study used an online platform-based test, observation and documentation. The results of the research in the first cycle of cognitive learning outcomes of students from the 1st meeting to the 2nd meeting achieved classical completeness of 54.5% and 68.2% with an average classical value of 72 and 76, and the quality of the learning process was predicated quite well. In cycle II, the cognitive learning outcomes of students from the 1st meeting to the 2nd meeting achieved classical completeness of 72.7% and 81.2% with good quality of the learning process. However, the average value of learning outcomes in the second cycle only reached 82.7 at the 2nd meeting. This research has not been said to be successful because the average has not reached 85 so that it is continued in cycle III. The stabilization of learning using the flipped classroom model in the third cycle obtained satisfactory results, namely the achievement of the average score at the end of the third cycle exceeded the success indicator, which was 89.1 while the percentage of classical completeness of cognitive learning outcomes reached 100% supported by the quality of learning which had a very good predicate. Based on this research, it can be concluded that the application of the flipped classroom model can improve students' cognitive learning outcomes. Keywords: learning outcomes, flipped classroom model, online learning Diterima pada : 1  Mei 2021;  Di-review pada: 3 Mei 2021; Disetujui pada:  4 Juni 2021   Diterima pada : 1  Mei 2021;  Di-review pada: 3 Mei 2021; Disetujui pada:  4 Juni 2021   Abstrak :Tujuan penelitian ini untuk mendeskripsikan peningkatan hasil belajar kognitif siswa kelas III SDN 4 Telukwetan melalui model flipped classroom pada pembelajaran daring Tema 8 Praja Muda Karana. Subjek penelitian tindakan kelas ini yaitu hasil belajar kognitif siswa sebanyak 22 siswa yang didukung dengan kualitas proses proses pembelajaran. Pengumpulan data pada penelitian ini menggunakan tes berbasis platform online, observasi dan dokumentasi. Hasil penelitian pada siklus I hasil belajar kognitif siswa dari pertemuan ke-1 ke pertemuan ke-2 mencapai ketuntasan klasikal 54,5% dan 68,2% dengan rerata nilai klasikal 72 dan 76, dan kualitas proses pembelajaran berpredikat cukup baik. Pada siklus II hasil belajar kognitif siswa dari pertemuan ke-1 ke pertemuan ke-2 mencapai ketuntasan klasikal 72,7% dan 81,2% dengan kualitas proses pembelajaran berpredikat baik. Namun rerata nilai hasil belajar di siklus II hanya mencapai 82,7 pada pertemuan ke-2. Penelitian ini belum dikatakan berhasil karena rerata belum mencapai 85 sehingga dilanjutkan pada siklus III. Pemantapan pembelajaran menggunakan model flipped classroom pada siklus III memperoleh hasil yang memuaskan yaitu pencapaian rerata nilai pada akhir siklus III melebih indikator keberhasilan yaitu mencapai 89,1 sementara persentase ketuntasan klasikal hasil belajar kogntif mencapai 100% didukung dengan kualitas pembelajaran yang berpredikat sangat baik. Berdasarkan penelitian ini dapat disimpulkan penerapan model flipped classroom dapat meningkatkan hasil belajar kognitif siswa.Kata kunci: hasil belajar,  model flipped classroom, pembelajaran daring